N-Acetylcysteine Augmentation in Children and Adolescents Diagnosed With Treatment-Resistant Obsessive-Compulsive Disorder Case Series - Yazici, Kemal Utku; Percinel, Ipek (Lippincott Williams & Wilkins, 2015)
[Abstract Not Available]
Keywords: Glutamatergic Dysfunction; Operational Definitions; Methodological Issues; Acetyl Cysteine; Ocd